Tinnitus and cognition: Can load theory help us refine our understanding?. Issue 6 (16th November 2020) - Khan, Rafay A.; Husain, Fatima T.
Abstract: Objective : Tinnitus has been shown to be associated with specific cognitive deficits. Contemporary models of tinnitus, based primarily on human behavior, emphasize the influence of the cognitive response to tinnitus in tinnitus manifestation and level of associated annoyance. The models and hypotheses proposed thus far have (a) focused on the cognitive response to the onset of tinnitus, and not necessarily focused on the cognitive consequences of established chronic tinnitus, and (b) failed to dissociate the contributions of cognitive and perceptual load in their theories. Load theory states that we have a limited capacity of neural resources that can be used to process internal and external stimuli. This theory is differentially applied to perceptual load, which refers to the neural resources engaged in the processing of sensory stimuli in our environment, and cognitive load, which refers to the occupation of a more central resource that is involved in higher‐level processing, such as stimulus discrimination, decision making, and working memory processing. Methods : A focused review was conducted on behavioral and brain‐imaging studies examining cognitive deficits in tinnitus, in an attempt to reexamine the findings in a load theory framework. Results : Findings of these studies are discussed in the context of load theory, and a novel model for understanding these findings is proposed. Conclusion : We believe the incorporation of load theory into models of tinnitus may advance understanding of the cognitive impact of tinnitus and lead to better management of tinnitus. Abstract :